An Introduction to Nuclear Waste Immobilisation - Ojovan,MI; Lee,WE (Elsevier, 2005)
The book thoroughly covers all issues surrounding nuclear waste: from where to locate nuclear waste in the environment, through nuclear waste generation and sources, treatment schemes and technologies, immobilisation technologies and waste ...